DESIGN OF AN EDUCATIONAL CENTER FOR RECYCLING INORGANIC WASTE USING AN ENERGY-SAVING ARCHITECTURAL APPROACH - Kindi Sisnanto; Nurina Vidya Ayuningtyas S. T., M.Sc (Architectural Research Journal, 2024)
Environmental damage caused by waste occurs in Yogyakarta, starting with the closure of the Piyungan Final Disposal Site due to excess cargo that caused the city of Yogyakarta to experience an emergency condition rubbish. Responding to this, the Yogyakarta City government implementing zero inorganic waste rules starting January 2023. Where people are prohibited from throwing away inorganic waste and are encouraged to manage it independently or through a bank rubbish. However, in practice, society does not have it education about managing inorganic waste and waste banks has its own obstacles in managing inorganic waste. Through the Inorganic Waste Recycling Education Center, the aim is provide a formulation of the concept for designing public facilities serves to educate the public about recycling inorganic waste. Using data collection methods namely qualitative methods with the aim of this research being, to produced a concept for designing a Recycling Education Center Inorganic Waste that uses an Economical Architecture approach Energy to maximize the sustainability of life in the future will come. And help the government in efforts to reduce it waste volume in Yogyakarta City.